PREVALANCE AND PREDICTORS OF MICROALBUMINURIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - SANGEETHA DAYANIDHI; K.RAMADEVI; I. PERIYANDAVAR (International Journal of Pharma and Bio Sciences, 2013)
Microalbuminuria represents the earliest clinical evidence of diabetic nephropathy. Early detection of microalbuminuria and early control of diabetes retards the development of structural changes in early diabetic nephropathy. This study aimed to determine the prevalence and correlation of microalbuminuria with age, duration of diabetes, sex and BMI in type 2 diabetic patients. 100 diabetic patients (48 male and 52 female) of age 40-75years were included in this study. Fasting blood samples and morning urine samples were collected for analysis of glucose, urea, creatinine and microalbumin respectively. Statistical analysis was done in SPSS version 13. Prevalence of microalbuminuria in this study is found to be 51%. Microalbumin had a highly significant correlation with age, duration of diabetics and body mass index (BMI). The high prevalence (51%) of microalbumin observed in these patients is alarming and indicates an impending pandemic of renal disease.